ASSOCIATION BETWEEN MID-UPPER ARM CIRCUMFERENCE AND HEMOGLOBIN CONCENTRATION IN ADOLESCENT GIRLS: A CROSS-SECTIONAL STUDY - Luh Putri Wulandari dewi; Sri Ratna Dewi; Ni Wayan Armerinayanti dewi; Desak Putu Oki Lestari dewi; Putu Indah Budi Apsari dewi; Kadek Agus Kurniawan; Dewa Ayu Agung Alit Suka Astini (Meditory : The Journal of Medical Laboratory, 2026)
Background: Anemia remains a relevant nutritional concern among adolescent girls. Mid-upper arm circumference (MUAC) is a practical anthropometric measurement that may be associated with hemoglobin concentration and may help identify adolescents with limited nutritional reserves. Objective: This study aimed to examine the association between MUAC length and hemoglobin concentration in adolescent girls at SMA N 1 Tegalalang, Gianyar Regency. Methods: This analytical observational study used a cross-sectional design. A total of 147 female students were recruited using consecutive sampling. MUAC was the independent variable, and hemoglobin concentration was the dependent variable. Hemoglobin was measured using a point-of-care testing device. Data were analyzed using ANCOVA in IBM SPSS Statistics version 27, with the control of age and menstrual duration. Results: Most participants had a MUAC of ≥23.5 cm (50.34%) and normal hemoglobin concentration (≥12 g/dL; 93.9%). After adjustment for age and menstrual duration, MUAC was significantly associated with hemoglobin concentration (F = 5.257, p = 0.024, partial η² = 0.047). Conclusions: A significant association was observed between MUAC and hemoglobin concentration among female adolescents. MUAC may be considered a practical anthropometric measure for identifying adolescents who could benefit from further nutritional assessment and hemoglobin testing.